Four new species from Venezuela and identification key to Cephalocarpus (Cryptangieae, Cyperaceae) - Costa, Suzana Maria; Thomas, William Wayt; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2024)
In this paper, we describe four new species of the sedge genus Cephalocarpus (Cryptangieae, Cyperaceae) from the Guiana Shield based on specimens collected before 1985. We provide an identification key to all species of Cephalocarpus. For the new species, we provide illustrations of diagnostic characters, distribution maps and additional comments.